2021
DOI: 10.1002/term.3257
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of mesenchymal stem cells cultured as cell‐only aggregates and in encapsulated hydrogels

Abstract: There is increasing evidence that cells cultured in three-dimensional (3D) settings have superior performance compared to their traditional counterparts in monolayers. This has been attributed to cell-cell and cell-extracellular matrix interactions that more closely resemble the in vivo tissue architecture. The rapid adoption of 3D cell culture systems as experimental tools for diverse applications has not always been matched by an improved understanding of cell behavior in different 3D environments. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Most importantly, the capsule system did allow for cell survival and proliferation. An attenuated proliferation had been previously reported for MSCs maintained in spheroids [ 37 , 38 ], but next to maintaining a high viability, we also confirmed actively proliferating cells after the initial condensation phase. A 2.5-fold increase in cell numbers was achieved over the four days of cultivation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Most importantly, the capsule system did allow for cell survival and proliferation. An attenuated proliferation had been previously reported for MSCs maintained in spheroids [ 37 , 38 ], but next to maintaining a high viability, we also confirmed actively proliferating cells after the initial condensation phase. A 2.5-fold increase in cell numbers was achieved over the four days of cultivation.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, in both groups, the signal shows a four–five-fold increase until days 2–3 but stays at that level or even decreases until day 4 ( Figure 6 C). There have been reports of MSCs cultured in spheroids attenuate proliferating after compacting [ 37 , 38 ]. Therefore, to investigate the proliferative behavior of the aggregated cells after this initial compaction phase, we performed EdU proliferation staining on days 2 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the 3D culture of stem cells includes self-assembly aggregation and encapsulation by hydrogel microspheres. Passanha et al found that cells encapsulated by alginate hydrogel exhibited better viability on the 14th day, probably because the alginate gel could provide more room for cells and allow for the diffusion of more nutrients and oxygen [ 197 ].…”
Section: Novel Applications Of Microspheres For Bone Tissue Engineeringmentioning
confidence: 99%
“…After illustrating spheroid fusion in these hydrogels, we subsequently investigated hMSC proliferation capacity within the different formulations. Previous studies have shown that proliferation rates are different in 2D and 3D, and many cell lines show reduced proliferation in 3D spheroid cultures 62 and hydrogels (synthetic and natural) [65][66][67] compared to 2D monolayer cultures. The type of matrix 66 and stress relaxation 18 also have been shown to influence the proliferation rates for cells.…”
Section: Biomaterials Science Papermentioning
confidence: 99%